Answer:
Hypotenuse² = Base² + Altitude²
35² = 15² + x²
1225 = 225 + x²
x² = 1225 - 225
x² = 1000
<u>X = 10√10</u>
Answer:
IJ= 4.98
Step-by-step explanation:
EF = 12
KF = 6
LF = 7.8
LK = sqrt(7.8^2-6^2) = 4.98
IJ = LK (4.98)
5.
f(K) = D^3 => f(25) = 125 => 25 * t = 125 ( because K is directly proportional with D^3 )=> t = 125 / 25 => t = 5 => f(25) = 25 * 5 => K * 5 = D^3 ;
6.
f(L) = F^3 => f(2) =3^3 =>f(2) = 27 => 2 / t =27 => t = 2 / 27 => t = 0.074 => f(2) = 2 / 0.074 => K / 0.074 = F^3 ;
Answer:
f ( - 2 ) = - 2
Step-by-step explanation:
Step 1:
f ( x ) = 3x + 4 Equation
Step 2:
f ( - 2 ) = 3 ( - 2 ) + 4 Input x value
Step 3:
f ( - 2 ) = - 6 + 4 Combine Like Terms
Answer:
f ( - 2 ) = - 2 Combine Like Terms
Hope This Helps :)
6z-7z/5=3
(30z-7z)/5=3
30z-7z=15
23z=15
z=15/23